Kondisi dan Kebutuhan Jalur Pejalan Kaki di Kawasan Permukiman Rappocini, Kota Makassar - Andi Ardi Mansyur; Shirly Wunas; Yusni Mustari (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
The development of residential areas in Makassar City also has an impact on the increasing pedestrian modes, one of which is in the Rappocini Settlement Area. Pedestrian paths that are not balanced with adequate service facilities cause overlapping in their use, so as not to provide comfort, safety, and smooth movement for pedestrians. This study aims to identify conditions and availability of pedestrian paths, demand patterns for pedestrian movements, and arrange direction of pedestrian paths on Jalan Landak Baru. This study is supported by a literature review to compare existing conditions with standards. Furthermore, the pedestrian movement request pattern is illustrated through the origin and destination of the trip, distance traveled, and walking companions obtained based on the results of in-depth interviews (questionnaire). Sampling is done by accident (accidental sampling). The analytical method used is comparative analysis, descriptive qualitative, quantitative descriptive, and conceptual. Based on the results of the analysis, the pedestrian path (sidewalk) meets the safety aspect, where the sidewalk is separate from the vehicle traffic lane and has a higher height than the road floor. The pattern of pedestrian movements based on the origin and destination of the trip, dominantly originating from home and aiming at educational facilities. Based on walking distance, pedestrians tend to travel> 500 meters. Based on walking companions, pedestrians tend to choose to walk on their own. Therefore, pedestrian paths are planned based on needs in order to increase accessibility, safety, comfort, beauty, convenience, and social interaction.